A COMPARATIVE STUDY OF FETOMATERNAL OUTCOMES IN PRIMARY CAESAREAN SECTION IN PRIMIGRAVIDA AND MULTIGRAVIDA - Dr.Devarasetty Lakshmi Naga Prathyusha; Dr.B.Balaji Naik; Dr.E.Lavanya Bai; Dr.K.Radha (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Objectives: To analyze the fetal and maternal outcomes in primigravida and multigravida who underwent primary caesarean section.Methods: This observational, prospective study was conducted at a tertiary care hospital in Tirupati. 150 prmigravida and 150 multigravida women who underwent primary caesarean section were included.Results: Most common indication in both the groups was fetal distress (32% of primigravida and 25% of multigravida). 14% and 32% multigravida women required blood transfusion and Iron sucrose infusions respectively. In 2.67% multigravida women, angle extension occurred intraoperatively. 18% multigravida women had surgical site infections. Post operative ileus was more in primigravida women (11.3%). RDS incidence was more in babies born to multigravida women (13.3%), whereas Birth asphyxia was more in babies born to primigravida women (7.3%)Conclusion: The above insights help in understanding the need of good antepartum, intrapartum and postpartum care to reduce maternal and perinatal mortality and morbidity. Evidence based practices along with caesarean section audit can reduce caesarean section rates.